Fulfillment of People With Severe Disabilities Rights - Hari Harjanto Setiawan; Bambang Pudjianto (Jurnal Penelitian Kesejahteraan Sosial, 2017)
Persons with severe disabilities (PDB) as a matter of fact are disabled indeed and their disabilities are not possible to be rehabilitated, thus they can not perform their daily life activities and or throughout their life they depend on the help of others, and they are unable to support their own life by themselves. It describes that persons with severe disabilities depend on and need the help of others along their life in fulfilling their rights. Fulfillment of their rights is somewhat expected much from their family. This study is quantitative research that will address the fulfillment of their rights from their family can be measured by two important indicators, namely the family economy and the family competence. This research was conducted in Jepara which is one of the ASPDB beneficiaries region. The results of this study answer the hypothesis thatthe influence of family economic condition towards the fulfillment of the persons with severe disabilities rights (PDB) is very little compared to the influence of family competences towards the fulfillment of the PDB rights.